DUTIES AND AUTHORITY OF A NOTARY IN PRODUCING LAND DEEDS - Asti, Natasya Rizki; Arsin, Fransiscus Xaverius (Awang Long Law Review, 2023)
Case Study 179/PDT.G/2022/PN.PLG is used to examine the roles and responsibilities of notaries in the creation of land deeds. Two primary lines of inquiry emerge from this statement of need for more study: (1) what are the responsibilities and powers of a notary in producing land deeds, and (2) what is the notary's responsibility for the land deeds he makes? A normative judicial methodology was used for this study. The result of this research is a notary's power to create land deeds is limited by Article 15 of the Law on the Position of Notaries. In compliance with legal mandates like the Government Regulation on PPAT, the Land Deed Making Officer (PPAT) is also empowered to create land deeds. A notary's ability to create certain property deeds, such as a Sale and Purchase Agreement Deed, is constrained by the PPAT's duties. The notary's obligation for land deeds depends on the cause of the inaccuracy. If the notary's mistake causes financial harm, the victim may file a civil lawsuit against the official. The UUJN also suggests possible criminal and administrative consequences, such as temporary termination. If the notary has followed all applicable laws and regulations and an honest mistake has occurred, the notary is immune from liability. This study's findings give a summary of the complexities involved in notaries' roles in drafting property deeds and fulfilling their obligations under relevant laws.